(3dGejI GdYLes - (3GdWZQGFj GdCUHgGfj, CHh ESeGYjd, eDjO GdOjf, GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO, (B513 (3g`s
(3ChdgG (B:s
(3CUGdI GdQCj UGfJfj Yf GdNWd (B*** (3hMdjI GdaVd RGfJfj dOi GdYWd , eLOj CNjQG heLOj ChdG TQY (B*** (3hGdTeS QCO GdVMi cGdTeS aj GdWads
(3BNQgG (B:s
(3hjG NHjQ Ydi GdCSQGQ eWdYG (B*** (3GUeJ aaj GdUeJ efLGI ef GdRdd , bO QTMhc dCeQ dh aWfJ dg (B*** (3aGQHC HfaSc Cf JQYi Y Gdgeds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 246s
(3eYLe GdeDdajf(B: 1 / 628s
(3cTa GdXfhf(B: 2 / 1537s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs